Physical Examination Has Been Paid Less Attention to Compared to Diagnostic Imaging: from a Bibliometric Analysis of PubMed. (25th March 2016) - Mizuno, Atsushi; Kawai, Fujimi; Shimizu, Taro
Abstract : Physical examination is still needed in this modern era in spite of the recent development of advanced imaging modalities. However, not only clinicians but also researchers (including clinical researchers) seem to pay less attention to physical examination as a research topic. A PubMed search revealed that instead of an increasing percentage of diagnostic imaging articles, there were decreasing percentages of physical examination articles, especially in Japan. We should reconsider physical examinations as an important research topic, which might be especially interesting for general internal medicine doctors.